User interface design of a sengkedan concept-based digital test - Agus Adiarta; Dewa Gede Hendra Divayana; I Putu Wisna Ariawan; P. Wayan Arta Suyasa; Made Susi Lissia Andayani; I Nyoman Indhi Wiradika (International Journal of Advances in Applied Sciences, 2024)
This study’s purpose was to demonstrate the design of a digital test for the “educational evaluation” course based on the sengkedan (swales) concept that has good quality. This research approach was a development that used the Borg and Gall model with more focus on the design development stage, initial design trials, and revisions. Subjects involved in the initial testing of the digital test user interface design were 42 respondents. The tool used to conduct initial testing of the digital test user interface design is a questionnaire. The data analysis technique used in this research was descriptive quantitative. The results showed user interface design of a sengkedan concept-based digital test for the “educational evaluation” course was quite good. The impact of this research on evaluators in the education field was a positive thing that added to their insights in developing a digital test. The evaluators will finally understand the importance of designing the user interface before finalizing the physical application to minimize errors.